A method for preparing long carbon chain nylon salt and its application
By dissolving and neutralizing the method of separately forming salts in aqueous solution and re-neutralizing reactions, combined with the adsorbent to remove impurities, the problems of high temperature and high pressure and organic solvent use in the preparation of long-carbon chain nylon salts in the prior art are solved, and the preparation of nylon salts with high efficiency and low energy consumption is achieved, and the purity and quality of the product are improved.
Patent Information
- Application Number
- CN202111232453.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-10-22
AI Technical Summary
In the preparation of long-carbon chain nylon salts, organic solvents or high-temperature and high-pressure conditions are required, resulting in problems such as long polymerization time, high energy consumption, unstable polymerization, and easy oxidation. At the same time, the residue of macromolecular organic compounds during the preparation process affects the quality of nylon.
Long carbon chain nylon salt is prepared by dissolving and neutralizing the reaction separately in aqueous solution. The nylon salt powder is obtained by filtration and drying, and impurities are removed during the reaction process and purity is improved.
It effectively avoids problems caused by high temperature and high pressure and organic solvents, shortens polymerization time, reduces energy consumption, and improves the purity of nylon salt and the quality of the produced nylon products.
Smart Images

Figure BDA0003316518670000111 
Figure BDA0003316518670000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a method for preparing long carbon chain nylon salt and application thereof. Background Art
[0002] Polyamide, also known as nylon (PA), is a nitrogen-containing heterochain polymer with a polyamide characteristic group (-NHCO-) in the main chain. It has the advantages of high mechanical strength, corrosion resistance, wear resistance, and easy processing. It is a general-purpose engineering plastic. As a long-chain nylon, PA1212 has the following unique properties in addition to the excellent properties of ordinary nylon: low water absorption, good dimensional stability, low relative density, self-lubricating, low temperature resistance, excellent impact resistance, etc., so it is widely used in mechanical equipment, electronics and electrical, textiles, aerospace, food and drug packaging, and powder coating manufacturing. Since long-chain nylon materials are widely used in the fields of automobiles, aerospace, electronics and electrical, etc., the research on the preparation method of long-chain nylon is of great significance.
[0003] Using nylon salt as a precursor for nylon polymerization can control the equimolar ratio of diamine and diacid, which is beneficial to control the polymerization process and improve repeatability. At present, there are two most common methods for preparing nylon 1212 salt. One is to use ethanol as a solvent, dissolve dodecanediamine and dodecanedioic acid in an ethanol solvent at a certain temperature, and then add the diamine solution dropwise to the dibasic acid solution with an equimolar ratio, and a neutralization reaction occurs to precipitate solids. After filtering and drying, nylon salt powder is obtained. This method is relatively simple and easy to operate, but the dibasic acid will also react with ethanol during the reaction, and the generated acid ester will have an adverse effect on the nylon polymerization reaction, and the recovery of ethanol requires distillation, resulting in an increase in energy consumption and cost. The other is water as a solvent, but the solubility of dodecanediamine and dodecanedioic acid in water is extremely small at room temperature and pressure, so this method needs to be carried out under high temperature and high pressure. This method consumes a lot of energy, and some side reactions may occur under high temperature and high pressure, affecting the subsequent nylon polymerization reaction.
[0004] Moreover, the raw materials for preparing long carbon chain nylon salts currently available on the market, such as dodecanediamine and dodecanedioic acid, are mostly prepared by biological fermentation, and the preparation process will produce macromolecular organic compounds and cause residues, which will affect the quality of the nylon produced. For example, cross-linking reactions will occur during the polymerization process, which will affect the quality of nylon. Moreover, these macromolecular organic compounds are difficult to dissolve in water, so it is difficult to effectively remove them using the method of using water as a solvent in the prior art, resulting in low purity of the prepared long carbon chain nylon salt, which further affects the quality of nylon. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing long carbon chain nylon salt, which can not only effectively avoid the problems of long polymerization time, high energy consumption, unstable polymerization, easy oxidation, etc. caused by the use of organic solvents or high temperature and high pressure conditions in the prior art, but also can effectively improve the purity of nylon salt and further improve the quality of the obtained nylon product.
[0006] To this end, the first aspect of the present invention provides a method for preparing a long carbon chain nylon salt, which comprises the following steps:
[0007] (1) subjecting a diamine and an inorganic acid to a first reaction, followed by first mixing with an optional first adsorbent, and filtering to obtain a diamine acid salt solution;
[0008] (2) subjecting the dibasic acid and the inorganic base to a second reaction, followed by a second mixing with an optional second adsorbent, and filtering to obtain a dibasic acid salt solution;
[0009] (3) subjecting the obtained diamine acid salt solution and the obtained dibasic acid salt solution to a third reaction, filtering, and drying to obtain nylon salt powder;
[0010] The diamine is at least one aliphatic diamine having ≥8 carbon atoms between two carbon atoms connected to an amino group on the main carbon chain, and / or the dibasic acid is at least one aliphatic dibasic acid having ≥8 carbon atoms between two carbon atoms connected to a carboxyl group on the main carbon chain.
[0011] According to some embodiments of the present invention, the diamine is selected from at least one aliphatic diamine having 10-20 carbon atoms between two carbon atoms connected to an amino group on the main carbon chain.
[0012] According to some embodiments of the present invention, the diamine is selected from at least one aliphatic diamine having 10-16 carbon atoms between two carbon atoms connected to an amino group on the main carbon chain.
[0013] According to some embodiments of the present invention, the diamine is dodecanediamine.
[0014] According to some embodiments of the present invention, the dibasic acid is selected from at least one aliphatic dibasic acid having 8 to 18 carbon atoms between two carbon atoms connected to a carboxyl group on the main carbon chain.
[0015] According to some embodiments of the present invention, the dibasic acid is selected from at least one aliphatic dibasic acid having 8 to 14 carbon atoms between two carbon atoms connected to a carboxyl group on the main carbon chain.
[0016] According to some embodiments of the present invention, the dibasic acid is dodecanedioic acid.
[0017] According to some embodiments of the present invention, the diamine is selected from C 10 -C 22 At least one aliphatic diamine, preferably selected from C 12 -C 18 At least one of aliphatic diamines.
[0018] According to some embodiments of the present invention, the dibasic acid is selected from C 12 -C 22 At least one of the aliphatic dibasic acids, preferably selected from C 12 -C 18 At least one of aliphatic dibasic acids.
[0019] According to some embodiments of the present invention, in the diamine, two amino groups are respectively located at two end positions of the diamine.
[0020] According to some embodiments of the present invention, in the dibasic acid, two carboxyl groups are respectively located at two end positions of the dibasic acid.
[0021] According to some embodiments of the present invention, in step (1), the amount of the inorganic acid used is such that the pH of the diamine acid salt solution is 5.5 to 6.5, such as 5.5, 6.0, 6.5 and any value therebetween.
[0022] According to some embodiments of the present invention, in step (2), the amount of the inorganic base is such that the pH of the dibasic acid salt solution is 7.5 to 8.5, such as 7.5, 8.0, 8.5 and any value therebetween.
[0023] According to some embodiments of the present invention, the molar ratio of the diamine in step (1) to the dibasic acid in step (2) is (1.01-1.10):1. In some preferred embodiments, the molar ratio of the diamine in step (1) to the dibasic acid in step (2) is (1.01-1.05):1.
[0024] According to some embodiments of the present invention, the inorganic acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid, preferably 36-38 wt % hydrochloric acid.
[0025] According to some embodiments of the present invention, the inorganic base is selected from at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate and sodium carbonate, preferably 50-90 wt % of sodium hydroxide.
[0026] According to some embodiments of the present invention, the temperature of the first reaction is 20-60°C, preferably 30-50°C.
[0027] According to some embodiments of the present invention, the time of the first reaction is 2 to 5 hours.
[0028] According to some embodiments of the present invention, the temperature of the second reaction is 20-60°C, preferably 30-50°C.
[0029] According to some embodiments of the present invention, the time of the second reaction is 1 to 3 hours.
[0030] According to some embodiments of the present invention, the temperature of the third reaction is 30-50°C.
[0031] According to some embodiments of the present invention, the third reaction is carried out for 2 to 6 hours.
[0032] According to some embodiments of the present invention, the temperatures of the first reaction, the second reaction and the third reaction are the same.
[0033] In the present invention, "optional" means containing or adding any amount, and the amount contained or added can be adjusted as needed, or not contained or added. For example, in step (1) and / or step (2), according to the need to improve the purity during the preparation process, no adsorbent can be added and only filtering can be performed, or any required amount of adsorbent can be added as needed before filtering.
[0034] According to some embodiments of the present invention, the time for the first mixing and / or the second mixing is 1-2 hours.
[0035] The adsorbent in the present invention is used to remove impurities contained in the raw materials or generated during the reaction, such as macromolecular organic compounds contained in long-chain diamines and / or long-chain dibasic acids (which will remain and, if not removed during the salt formation process, will undergo cross-linking reactions during the polymerization process, affecting the quality of nylon 1212 resin).
[0036] In some preferred embodiments, the first adsorbent and the second adsorbent are the same or different, and are independently selected from at least one of activated carbon, diatomaceous earth, and molecular sieves.
[0037] According to some embodiments of the present invention, the amount of the first adsorbent used is 0.5-2.0 wt % based on the mass of the diamine.
[0038] According to some embodiments of the present invention, the amount of the second adsorbent used is 0.5-1.0 wt % based on the mass of the dibasic acid.
[0039] According to some embodiments of the present invention, the filtering is performed through filter paper or a stainless steel filter mesh.
[0040] According to some embodiments of the present invention, the mesh size of the stainless steel filter is not particularly limited, as long as it can filter out the precipitate in the salt generated by the reaction.
[0041] According to some embodiments of the present invention, the long carbon chain nylon salt is prepared by the following steps:
[0042] (a) slowly adding concentrated hydrochloric acid (36-38 wt%) to the aqueous suspension of dodecanediamine, reacting at 20-60° C. for 2-5 hours, adjusting the pH to 5.5-6.5, filtering directly or adding activated carbon (or diatomaceous earth) and continuing stirring for 1-2 hours and then filtering to obtain a clear and transparent dodecanediamine hydrochloride solution;
[0043] (b) slowly adding sodium hydroxide solution (50-90 wt%) to the aqueous suspension of dodecanedioic acid, reacting at 20-60° C. for 1-3 hours, adjusting the pH to 7.5-8.5, filtering directly or adding activated carbon (or diatomaceous earth) and continuing stirring for 1-2 hours and then filtering to obtain a clear and transparent sodium salt solution of dodecanedioic acid;
[0044] (c) Adding a dodecanediamine hydrochloride solution to a dodecanedicarboxylic acid sodium salt solution, wherein the molar amount of the diamine is 1.01 to 1.05 times that of the dicarboxylic acid, a long carbon chain nylon salt is precipitated from the solution, and stirring is continued at 30 to 50° C. for 3 to 6 hours. The nylon salt powder is filtered and dried while hot to obtain the nylon salt powder.
[0045] The second aspect of the present invention provides an application of the method described in the first aspect of the present invention in the preparation of nylon 1212.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] 1) The method of the present invention for preparing long carbon chain nylon salt by dissolving the salt in an aqueous solution and then neutralizing the salt, effectively avoids the problems of long polymerization time, high energy consumption, unstable polymerization, easy oxidation, etc. caused by the use of organic solvents or high temperature and high pressure conditions in the prior art.
[0048] 2) The scheme of the present invention can effectively remove residual macromolecular organic compound impurities by the method of first forming salts and then filtering, thereby improving the purity of long carbon chain nylon salts. The nylon resin obtained by polycondensation has low relative viscosity and high processability. DETAILED DESCRIPTION
[0049] To make the present invention easier to understand, the present invention will be described in detail below in conjunction with the examples. It should be emphasized that the following description is exemplary only and should not be regarded as limiting the scope of the present invention. In the examples, if no specific conditions are specified, the conditions are carried out according to normal conditions or manufacturer recommendations. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially or obtained using conventional or open methods.
[0050] The relevant data in the embodiments of the present invention are obtained according to the following test method:
[0051] Purity test method: Ultra-high performance liquid chromatography (UPLC) was used to test the purity of the sample, and the peak area was statistically analyzed to obtain the sample purity.
[0052] Rheological viscosity test method: The high temperature rheological test uses Anton Paar's advanced rotational rheometer MCR302 to test the change of rheological viscosity with rotational shear rate under high temperature conditions.
[0053] Example 1
[0054] (1) 20.2 g of dodecanediamine (1,12-diaminododecane) and 100 g of pure water were added to a reaction bottle, heated to 40° C., concentrated hydrochloric acid (36-38 wt%) was slowly added, and the reaction was carried out at 40° C. for 3 hours. The pH was adjusted to 5.5, and the solution was filtered through filter paper to obtain a clear and transparent dodecanediamine hydrochloride solution;
[0055] (2) 23.0 g of dodecanedioic acid (1,10-decanedicarboxylic acid) and 200 g of pure water were added to a reaction bottle, heated to 40° C., and sodium hydroxide solution (70 wt %) was slowly added. The mixture was reacted at 40° C. for 2 hours, and the pH was adjusted to 8.0. The solution was filtered through filter paper to obtain a clear and transparent sodium salt solution of dodecanedioic acid;
[0056] (3) The obtained dodecanediamine hydrochloride solution was added dropwise to the sodium dodecanedioic acid solution, and the mixture was stirred and reacted. A white solid was precipitated. After the addition of the materials, the reaction was continued at 40°C for 3.0 hours. After the reaction was completed, the mixture was filtered while hot to obtain a white nylon salt powder. After sufficient drying, the yield was 91.8% and the purity was tested. The obtained nylon salt was added to a high-pressure reactor for polycondensation reaction. The conditions for the polycondensation reaction were: the ratio of nylon 1212 salt to water was 2:1, the amount of catalyst added was 0.1wt%, and the mixture was mixed evenly and added to a high-temperature and high-pressure polymerization reactor; after heating for one hour, the temperature was raised to 220°C, the pressure in the reactor was raised to 2.0MPa, and the temperature and pressure were maintained for two hours; the gas was slowly released, and the pressure in the reactor was reduced to normal pressure within two hours; the reaction temperature was maintained at 240°C under normal pressure, and the reaction was continued for two hours. The nylon 1212 resin was prepared and its rheological viscosity was measured. The purity and rheological viscosity results are shown in Table 1.
[0057] Example 2
[0058] (1) 20.2 g of dodecanediamine (1,12-diaminododecane) and 100 g of pure water were added to a reaction bottle, heated to 40° C., concentrated hydrochloric acid (36-38 wt%) was slowly added, and the reaction was carried out at 40° C. for 3 hours. The pH was adjusted to 6.5, and the solution was filtered through filter paper to obtain a clear and transparent dodecanediamine hydrochloride solution;
[0059] (2) 23.0 g of dodecanedioic acid (1,10-decanedicarboxylic acid) and 200 g of pure water were added to a reaction bottle, heated to 40° C., and sodium hydroxide solution (70 wt %) was slowly added. The mixture was reacted at 40° C. for 2 hours, and the pH was adjusted to 8.0. The solution was filtered through filter paper to obtain a clear and transparent sodium salt solution of dodecanedioic acid;
[0060] (3) The obtained dodecanediamine hydrochloride solution was added dropwise to the dodecanedioic acid sodium salt solution, and the mixture was stirred and reacted to precipitate a white solid. After the addition of the materials, the reaction was continued at 40°C for 3.0 hours. After the reaction was completed, the mixture was filtered while hot to obtain a white nylon salt powder. After sufficient drying, the yield was 92.6% and the purity was tested. The obtained nylon salt was added to a high-pressure reactor for polycondensation reaction. The polycondensation reaction conditions were the same as those in Example 1 to prepare nylon 1212 resin and measure its rheological viscosity. The purity and rheological viscosity results are shown in Table 1.
[0061] Example 3
[0062] (1) 20.2 g of dodecanediamine (1,12-diaminododecane) and 100 g of pure water were added to a reaction bottle, heated to 40° C., concentrated hydrochloric acid (36-38 wt %) was slowly added, and the reaction was carried out at 40° C. for 3 hours. The pH was adjusted to 6.0, and the solution was filtered through filter paper to obtain a clear and transparent dodecanediamine hydrochloride solution;
[0063] (2) 23.0 g of dodecanedioic acid (1,10-decanedicarboxylic acid) and 200 g of pure water were added to a reaction bottle, heated to 40° C., and sodium hydroxide solution (70 wt %) was slowly added. The mixture was reacted at 40° C. for 2 hours, and the pH was adjusted to 7.5. The solution was filtered through filter paper to obtain a clear and transparent sodium salt solution of dodecanedioic acid;
[0064] (3) The obtained dodecanediamine hydrochloride solution was added dropwise to the sodium dodecanedioic acid solution, and the mixture was stirred and reacted to precipitate a white solid. After the addition of the materials, the reaction was continued at 40°C for 3.0 hours. After the reaction was completed, the mixture was filtered while hot to obtain a white nylon salt powder. After sufficient drying, the yield was 92.4% and the purity was tested. The obtained nylon salt was added to a high-pressure reactor for polycondensation reaction. The polycondensation reaction conditions were the same as those in Example 1 to prepare nylon 1212 resin and measure its rheological viscosity. The purity and rheological viscosity results are shown in Table 1.
[0065] Example 4
[0066] (1) 20.2 g of dodecanediamine (1,12-diaminododecane) and 100 g of pure water were added to a reaction bottle, heated to 40° C., concentrated hydrochloric acid (36-38 wt %) was slowly added, and the reaction was carried out at 40° C. for 3 hours. The pH was adjusted to 6.0, and the solution was filtered through filter paper to obtain a clear and transparent dodecanediamine hydrochloride solution;
[0067] (2) 23.0 g of dodecanedioic acid and 200 g of pure water were added to a reaction bottle, heated to 40° C., and sodium hydroxide solution (70 wt %) was slowly added. The mixture was reacted at 40° C. for 2 hours, and the pH was adjusted to 8.5. The solution was filtered through filter paper to obtain a clear and transparent sodium salt solution of dodecanedioic acid;
[0068] (3) The obtained dodecanediamine hydrochloride solution was added dropwise to the dodecanedioic acid sodium salt solution, and the mixture was stirred and reacted to precipitate a white solid. After the addition of the materials, the reaction was continued at 40°C for 3.0 hours. After the reaction was completed, the mixture was filtered while hot to obtain a white nylon salt powder. After sufficient drying, the yield was 91.5% and the purity was tested. The obtained nylon salt was added to a high-pressure reactor for polycondensation reaction. The polycondensation reaction conditions were the same as those in Example 1 to prepare nylon 1212 resin and measure its rheological viscosity. The purity and rheological viscosity results are shown in Table 1.
[0069] Example 5
[0070] (1) 20.2 g of dodecanediamine (1,12-diaminododecane) and 100 g of pure water were added to a reaction bottle, heated to 50° C., concentrated hydrochloric acid (36-38 wt %) was slowly added, and the reaction was carried out at 50° C. for 3 hours. The pH was adjusted to 6.0, and the solution was filtered through filter paper to obtain a clear and transparent dodecanediamine hydrochloride solution;
[0071] (2) 23.0 g of dodecanedioic acid (1,10-decanedioic acid) and 200 g of pure water were added to a reaction bottle, heated to 50° C., and sodium hydroxide solution (70 wt %) was slowly added. The mixture was reacted at 50° C. for 2 hours, and the pH was adjusted to 8.0. The solution was filtered through filter paper to obtain a clear and transparent sodium salt solution of dodecanedioic acid;
[0072] (3) The obtained dodecanediamine hydrochloride solution was added dropwise to the dodecanedioic acid sodium salt solution, and the mixture was stirred and reacted to precipitate a white solid. After the addition of the materials, the reaction was continued at 50°C for 3.0 hours. After the reaction was completed, the mixture was filtered while hot to obtain a white nylon salt powder. After sufficient drying, the yield was 92.1% and the purity was tested. The obtained nylon salt was added to a high-pressure reactor for polycondensation reaction. The polycondensation reaction conditions were the same as those in Example 1 to prepare nylon 1212 resin and measure its rheological viscosity. The purity and rheological viscosity results are shown in Table 1.
[0073] Example 6
[0074] (1) 20.5 g of dodecanediamine (1,12-diaminododecane) and 100 g of pure water were added to a reaction bottle, heated to 40° C., concentrated hydrochloric acid (36-38 wt %) was slowly added, and the reaction was carried out at 40° C. for 3 hours. The pH was adjusted to 6.0, and the solution was filtered through filter paper to obtain a clear and transparent dodecanediamine hydrochloride solution;
[0075] (2) 23.0 g of dodecanedioic acid (1,10-decanedicarboxylic acid) and 200 g of pure water were added to a reaction bottle, heated to 40° C., and sodium hydroxide solution (70 wt %) was slowly added. The mixture was reacted at 40° C. for 2 hours, and the pH was adjusted to 8.0. The solution was filtered through filter paper to obtain a clear and transparent sodium salt solution of dodecanedioic acid;
[0076] (3) The obtained dodecanediamine hydrochloride solution was added dropwise to the dodecanedioic acid sodium salt solution, and the mixture was stirred and reacted to precipitate a white solid. After the addition of the materials, the reaction was continued at 40°C for 3.0 hours. After the reaction was completed, the mixture was filtered while hot to obtain a white nylon salt powder. After sufficient drying, the yield was 91.4%, and the purity was tested. The obtained nylon salt was added to a high-pressure reactor for polycondensation reaction. The polycondensation reaction conditions were the same as those in Example 1 to prepare nylon 1212 resin, and its rheological viscosity was measured. The purity and rheological viscosity results are shown in Table 1.
[0077] Example 7
[0078] (1) 21.0 g of dodecanediamine (1,12-diaminododecane) and 100 g of pure water were added to a reaction bottle, heated to 40° C., concentrated hydrochloric acid (36-38 wt %) was slowly added, and the reaction was carried out at 40° C. for 2 hours. The pH was adjusted to 6.0, and the solution was filtered through filter paper to obtain a clear and transparent dodecanediamine hydrochloride solution;
[0079] (2) 23.0 g of dodecanedioic acid (1,10-decanedicarboxylic acid) and 200 g of pure water were added to a reaction bottle, heated to 40° C., and sodium hydroxide solution (70 wt %) was slowly added. The mixture was reacted at 40° C. for 2 hours, and the pH was adjusted to 8.0. The solution was filtered through filter paper to obtain a clear and transparent sodium salt solution of dodecanedioic acid;
[0080] (3) The obtained dodecanediamine hydrochloride solution was added dropwise to the dodecanedioic acid sodium salt solution, and the mixture was stirred and reacted to precipitate a white solid. After the addition of the materials, the reaction was continued at 40°C for 3.0 hours. After the reaction was completed, the mixture was filtered while hot to obtain a white nylon salt powder. After sufficient drying, the yield was 91.5% and the purity was tested. The obtained nylon salt was added to a high-pressure reactor for polycondensation reaction. The polycondensation reaction conditions were the same as those in Example 1 to prepare nylon 1212 resin and measure its rheological viscosity. The purity and rheological viscosity results are shown in Table 1.
[0081] Example 8
[0082] (1) 21.0 g of 1,12-diaminododecane and 100 g of pure water were added to a reaction bottle, heated to 40° C., concentrated hydrochloric acid (36-38 wt%) was slowly added, and the mixture was reacted at 40° C. for 2 hours. The pH was adjusted to 6.0, 0.21 g of activated carbon was added to the solution, and stirring was continued for 1 hour. After filtering through filter paper, a clear and transparent 1,12-diaminododecane hydrochloride solution was obtained;
[0083] (2) 23.0 g of dodecanedioic acid and (1,10-decanedicarboxylic acid) 200 g of pure water were added to a reaction bottle, heated to 40° C., sodium hydroxide solution (70 wt %) was slowly added, and the mixture was reacted at 40° C. for 2 hours. The pH was adjusted to 8.0, 0.23 g of activated carbon was added to the solution, and stirring was continued for 1 hour. After filtering with filter paper, a clear and transparent sodium salt solution of dodecanedioic acid was obtained;
[0084] (3) The obtained dodecanediamine hydrochloride solution was added dropwise to the sodium dodecanedioic acid solution, and the mixture was stirred and reacted to precipitate a white solid. After the addition of the materials, the reaction was continued at 40°C for 3.0 hours. After the reaction was completed, the mixture was filtered while hot to obtain a white nylon salt powder. After sufficient drying, the yield was 91.2% and the purity was tested. The obtained nylon salt was added to a high-pressure reactor for polycondensation reaction. The polycondensation reaction conditions were the same as those in Example 1 to prepare nylon 1212 resin and measure its rheological viscosity. The purity and rheological viscosity results are shown in Table 1.
[0085] Example 9
[0086] (1) 21.0 g of dodecanediamine (1,12-diaminododecane) and 100 g of pure water were added to a reaction bottle, heated to 40° C., concentrated hydrochloric acid (36-38 wt%) was slowly added, reacted at 40° C. for 2 hours, the pH was adjusted to 6.0, 0.21 g of activated carbon was added to the solution and stirring was continued for 2 hours, and a clear and transparent dodecanediamine hydrochloride solution was obtained after filtering through filter paper;
[0087] (2) 23.0 g of dodecanedioic acid (1,10-decanedicarboxylic acid) and 200 g of pure water were added to a reaction bottle, heated to 40° C., and sodium hydroxide solution (70 wt %) was slowly added. The mixture was reacted at 40° C. for 2 hours, and the pH was adjusted to 8.0. 0.23 g of activated carbon was added to the solution and stirring was continued for 2 hours. After filtering with filter paper, a clear and transparent sodium salt solution of dodecanedioic acid was obtained;
[0088] (3) Add the dodecanediamine hydrochloride solution dropwise to the dodecanedioic acid sodium salt solution, react while stirring, and a white solid is precipitated by the reaction. After the addition of the materials, the reaction is continued at 40°C for 3.0 hours. After the reaction is completed, filter while hot to obtain a white nylon salt powder. After sufficient drying, the yield is 91.0%, and the purity is tested to be 99.3%. Add the nylon salt to an autoclave for polycondensation reaction. The polycondensation reaction conditions are the same as those in Example 1 to prepare nylon 1212 resin, and measure its rheological viscosity. The purity and rheological viscosity results are shown in Table 1.
[0089] Example 10
[0090] (1) 21.0 g of dodecanediamine (1,12-diaminododecane) and 100 g of pure water were added to a reaction bottle, heated to 40° C., concentrated hydrochloric acid (36-38 wt%) was slowly added, reacted at 40° C. for 2 hours, the pH was adjusted to 6.0, 0.21 g of diatomaceous earth was added to the solution, and stirring was continued for 2 hours. After filtering through filter paper, a clear and transparent dodecanediamine hydrochloride solution was obtained;
[0091] (2) 23.0 g of dodecanedioic acid (1,10-decanedicarboxylic acid) and 200 g of pure water were added to a reaction bottle, heated to 40° C., and sodium hydroxide solution (70 wt %) was slowly added. The mixture was reacted at 40° C. for 2 hours, and the pH was adjusted to 8.0. After 0.23 diatomaceous earth was added to the solution, stirring was continued for 2 hours. After filtering with filter paper, a clear and transparent sodium salt solution of dodecanedioic acid was obtained.
[0092] (3) The obtained dodecanediamine hydrochloride solution was added dropwise to the dodecanedioic acid sodium salt solution, and the mixture was stirred and reacted to precipitate a white solid. After the addition of the materials, the reaction was continued at 40°C for 3.0 hours. After the reaction was completed, the mixture was filtered while hot to obtain a white nylon salt powder. After sufficient drying, the yield was 91.1%, and the purity was tested to be 99.3%. The nylon salt was added to a high-pressure reactor for polycondensation reaction. The polycondensation reaction conditions were the same as those in Example 1 to prepare nylon 1212 resin, and its rheological viscosity was measured. The purity and rheological viscosity results are shown in Table 1.
[0093] Comparative Example 1
[0094] (1) Add 20.2 g of dodecanediamine (1,12-diaminododecane) and 30 g of ethanol into a three-necked flask, heat to 70° C., and stir to fully dissolve to obtain a hot ethanol solution of dodecanediamine;
[0095] (2) Add 23.0 g of dodecanedioic acid (1,10-decanedioic acid) and 120 g of ethanol into a three-necked flask, heat to 70° C., and stir to fully dissolve to obtain an ethanol solution of dodecanedioic acid;
[0096] (3) Add the hot ethanol solution of dodecanediamine dropwise to the ethanol solution of dodecanedioic acid, react while stirring, keep the reaction temperature at 70°C, continue the reaction for 3.0 hours after the addition of the materials, cool down to 25°C, filter to obtain white nylon salt, dry in a vacuum oven at 80°C, and after complete drying, test its yield to be 94.3% and purity to be 95.1%. Add the nylon salt to an autoclave for polycondensation reaction, the polycondensation reaction conditions are the same as those in Example 1, prepare nylon 1212 resin, and measure its rheological viscosity to be 37400.
[0097] Comparative Example 2
[0098] 20.2g of dodecanediamine (1,12-diaminododecane), 23.0g of dodecanedioic acid (1,10-decanoic acid) and 300g of pure water were added to a high-pressure reactor, heated to 140°C, stirred to fully dissolve, and reacted for 3.0 hours; the reaction was cooled to 25°C, solids precipitated from the solution, filtered, washed with ethanol, and white nylon salt was obtained, which was dried in a vacuum oven at 80°C. After complete drying, the yield was tested to be 96.8% and the purity was 93.2%. The nylon salt was added to the high-pressure reactor for polycondensation reaction. The polycondensation reaction conditions were the same as those in Example 1, and nylon 1212 resin was prepared, and its rheological viscosity was measured to be 54700.
[0099] Table 1
[0100]
[0101]
[0102] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a long carbon chain nylon salt, comprising the following steps: (1) subjecting a diamine and an inorganic acid to a first reaction, followed by a first mixing with a first adsorbent, and filtering to obtain a diamine acid salt solution; (2) subjecting the dibasic acid and the inorganic base to a second reaction, and then subjecting the dibasic acid and the inorganic base to a second mixing with a second adsorbent, and filtering to obtain a dibasic acid salt solution; (3) subjecting the obtained diamine acid salt solution and the obtained dibasic acid salt solution to a third reaction, filtering, and drying to obtain nylon salt powder; The diamine is selected from at least one aliphatic diamine with ≥8 carbon atoms between two carbon atoms connected to an amino group on the main carbon chain, and the dibasic acid is selected from at least one aliphatic dibasic acid with ≥8 carbon atoms between two carbon atoms connected to a carboxyl group on the main carbon chain.
2. The method according to claim 1, characterized in that: The diamine is selected from at least one aliphatic diamine having 10 to 20 carbon atoms between two carbon atoms connected to an amino group on the main carbon chain. And / or the dibasic acid is at least one selected from aliphatic dibasic acids having 8 to 18 carbon atoms between two carbon atoms connected to a carboxyl group on the main carbon chain.
3. The method according to claim 2, characterized in that The diamine is selected from at least one aliphatic diamine having 10 to 16 carbon atoms between two carbon atoms connected to an amino group on the main carbon chain; And / or, the dibasic acid is at least one selected from aliphatic dibasic acids having 8 to 14 carbon atoms between two carbon atoms connected to a carboxyl group on the main carbon chain.
4. The method according to any one of claims 1 to 3, characterized in that In step (1), the amount of the inorganic acid is such that the pH of the diamine salt solution is 5.5 to 6.
5. And / or in step (2), the amount of the inorganic base is such that the pH of the dibasic acid salt solution is 7.5 to 8.
5.
5. The method according to any one of claims 1 to 3, characterized in that: The molar ratio of the diamine in step (1) to the dibasic acid in step (2) is (1.01-1.10):
1.
6. The method according to claim 5, characterized in that The molar ratio of the diamine in step (1) to the dibasic acid in step (2) is (1.01-1.05):
1.
7. The method according to any one of claims 1 to 3, characterized in that The inorganic acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid; And / or the inorganic base is selected from at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate and sodium carbonate.
8. The method according to claim 7, characterized in that The inorganic acid is 36-38wt% hydrochloric acid; And / or the inorganic base is 50-90wt% sodium hydroxide.
9. The method according to any one of claims 1 to 3, characterized in that: The temperature of the first reaction is 20 to 60° C., and / or the time of the first reaction is 2 to 5 hours; and / or the temperature of the second reaction is 20 to 60° C., and / or the time of the second reaction is 1 to 3 hours; And / or the temperature of the third reaction is 30-50° C., and / or the time of the third reaction is 2-6 hours.
10. The method according to any one of claims 1 to 3, characterized in that: The first adsorbent and the second adsorbent are the same or different, and are independently selected from at least one of activated carbon, diatomaceous earth and molecular sieve.
11. The method according to claim 10, characterized in that The time for the first mixing and / or the second mixing is 1-2 hours.
12. The method according to any one of claims 1 to 3, characterized in that The amount of the first adsorbent is 0.5-2.0 wt % based on the mass of the diamine; and / or the amount of the second adsorbent is 0.5-1.0 wt % based on the mass of the dibasic acid.
13. The method according to any one of claims 1 to 3, characterized in that: The filtration is performed through filter paper or a stainless steel filter.
14. Use of the method according to any one of claims 1 to 13 in the preparation of nylon 1212.
Citation Information
Patent Citations
Preparation method of nylon salts
CN105924358A